Environmental Education in the Municipalities of Petroleum Sergipe: realities and pos-sibilities in Carmópolis and Pirambu - Silva, Phellipe Cunha da; Silva, Gicélia Mendes da (Geografares, 2016)
This study is the result of the dissertation presented at the Graduate Program in Development and Environment (PRODEMA) of the Federal University of Sergipe (UFS), research carried out from the restlessness about how environmental education effectively if the oil municipalities of Sergipe. To do this analysis we seek references in two municipalities of oil that we offered conditions comparison of possibilities for realization of environmental education. The chosen municipalities were Carmopolis and Pirambu. Carmopolis is a town where oil exploration takes place in onshore mode and the muni-cipality of Pirambu, this oil exploration occurs predominantly offshore. These differences are representative because of that, the type of operation is directly related to how the environment is impacted and also how this impact is perceived by the inhabitants. From the literature review and interviews it became clear that environmental education in the two counties can be carried out efficiently if there is involvement of all sectors of society.